2017
DOI: 10.2147/ott.s135593
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic values of Ki-67/MIB-1 expression in thyroid cancer: a meta-analysis with 6,051 cases

Abstract: BackgroundGrowing evidence has demonstrated that Ki-67/MIB-1 has an effect on the clinical progression and prognosis in cancers. However, the diagnostic and prognostic values of Ki-67/MIB-1 in thyroid cancer remain unclear.Materials and methodsThe meta-analysis was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were retrieved from PubMed, EBSCO, EMBASE, ISI Web of Science, China National Knowledge Infrastructure, WanFang and Chinese VIP datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
3
34
0
2
Order By: Relevance
“…The value of the Ki‐67 labeling index in CMV‐PTC cases is usually low, less than 6%; however, two of three cases of metastatic CMV‐PTC showed a high Ki‐67 labeling index. Previous reports indicated that a high Ki‐67 labeling index correlated with distant metastasis and an unfavorable prognosis . In our case, the Ki‐67 labeling indexes of thyroid (primary) and lung (metastasis) tumors were 40.2% and 22.1%, respectively; notably, the thyroid tumor in this study led to multiple lung metastases.…”
Section: Discussionsupporting
confidence: 56%
“…The value of the Ki‐67 labeling index in CMV‐PTC cases is usually low, less than 6%; however, two of three cases of metastatic CMV‐PTC showed a high Ki‐67 labeling index. Previous reports indicated that a high Ki‐67 labeling index correlated with distant metastasis and an unfavorable prognosis . In our case, the Ki‐67 labeling indexes of thyroid (primary) and lung (metastasis) tumors were 40.2% and 22.1%, respectively; notably, the thyroid tumor in this study led to multiple lung metastases.…”
Section: Discussionsupporting
confidence: 56%
“…; Pan et al . ). However, there was no significant difference of Ki‐67 expression between patients with tumour size ≤2 cm and >2 cm ( Z = −0.309, P = 0.757).…”
Section: Resultsmentioning
confidence: 97%
“…; Pan et al . ). In this study, we did not find an association between ERβ1 and Ki‐67, which was consistent with our previous findings (Huang et al .…”
Section: Discussionmentioning
confidence: 97%
“…The Ki67 proliferation index is widely used to assess the grade of tumor histological malignancy. This is correlated with cancer patient cell proliferation, time to recurrence and shorter survival rate [76]. Ki67 and the histological tumor grade are also correlated with changes in phenotype of lymph node metastases compared to the primary tumor, together with certain molecular markers associated with malignancy and a poorer prognosis [77].…”
Section: Adams As Diagnostic and Prognostic Markersmentioning
confidence: 97%